Legal Aspect of Foreign Direct Investment in Indonesia Based on the Law of Number 25 of the Year 2017 Concerning Investment - Sentosa Sembiring (Sociological Jurisprudence Journal, 2019)
Indonesia as a developing country in various sectors requires substantial funding. Government funds are very limited. One of the alternatives to move the wheels is to invite foreign investors. Aims of this research is to obtain legal certainty in making investments, the government renewed the legal basis of investment namely issuing Law Number 25 Year 2007 on Investment. In this law has been adopted from international agreements associated with the investment regime. In principle it is not an area of investment that can be entered by open investors in all areas. In order to have legal certainty the government issues a negative list of investments. To improve services to investors in this law is authorized by the Investment Coordinating Board to coordinate one-stop services.